Protocol for determining peak heart rates in swimmers - Coutts, A.; Dover, T.; Reaburn, P.; Schofield, G. (2001)
This study investigated three different swimming protocols and their effect on producing peak heart rates (HRpeak) in free pool swimming. Seven swimmers (mean 400-m swim time 312 ± 28 seconds, mean body mass 73.5 ± 10.1 kg, mean height 180.3 ± 8.0 cm and mean body fat percentage 10.5 ± 3.3 percent) participated in the study. Each subject completed three different swimming protocols to determine HRpeak. The trials were conducted in a randomised order with at least twenty-four hours between testing sessions. Heart rates were measured with a Treffene Heart Rate recorder. Additionally, the subjects rating of perceived exertion (RPE, Borg's Scale) were reported. The three protocols completed consisted of a 400-m performance trial; a 10 x 100-m interval trial and a 50-m incremental paced interval trial. The 10 x 100-m protocol recorded an average maximal heart rate of 187.6 ± 20.1 beats per minute (b.min-1); the second highest average recorded heart rate was the 50-m interval (184.7 ± 19.1 b.min-1). The 400-m continuous effort recorded the lowest average peak heart rate (180.4 ± 19.1 b.min-1). The 100-m protocol yielded significantly higher mean maximal heart rates, is simple to implement and can be easily applied to large groups. Collectively, these factors demonstrate the 100-m protocol as the ideal protocol for determining HRpeak in free pool swimming.